THE LINGUISTIC REFLECTION IN THE DIARIES BY METROPOLITAN VENIAMIN FEDCHENKOV 1926-1948 (Proceedings of Southern Federal University. Philology, 2014)
The article is devoted to the analysis of language reflection in metropolitan Veniamin Fedchenkov’ diaries. The focus is given to the linguistic means, which he uses to describe some events. The author studies different ways of word meaning actualization according to the morpheme meaning. Keywords: diary, linguistic reflection, word meaning actualization, morpheme.Author: Panova A.A.